1994
DOI: 10.2307/1131420
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Physically Abused and Nonabused Children to Different Forms of Interadult Anger

Abstract: Responses to various forms of interadult anger were examined in 2 groups of 6-11-year-olds: 44 low-SES children with a history of physical abuse and exposure to interspousal aggression, and 44 low-SES children exposed to interspousal aggression but with no history of physical abuse or other child maltreatment. Children were presented with videotaped segments of adults in angry and friendly interactions. Angry segments varied on (a) the type of anger expression (nonverbal, verbal, verbal-physical), and (b) whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 29 publications
4
46
1
Order By: Relevance
“…They also reported that certain childrearing practices appear to contributed to later outcomes, both as risk (e.g., inconsistency and overprotectiveness) and protective (e.g., providing structure during play and rational guidance of child behavior). Marital discord also influences the development of child emotion regulation, particularly if child abuse is occurring concurrently (e.g., Gottman & Katz, 1989;Hennessy, Rabideau, Cicchetti, & Cummings, 1994). For example, Gottman and Katz (1989) examined family, parental, and child-peer interactions along with several physio-logical indices of emotion processes (e.g., stress and emotion regulation) in families with varying levels of marital distress.…”
Section: Other Emotion Regulation Processes: Psychopathological Populmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that certain childrearing practices appear to contributed to later outcomes, both as risk (e.g., inconsistency and overprotectiveness) and protective (e.g., providing structure during play and rational guidance of child behavior). Marital discord also influences the development of child emotion regulation, particularly if child abuse is occurring concurrently (e.g., Gottman & Katz, 1989;Hennessy, Rabideau, Cicchetti, & Cummings, 1994). For example, Gottman and Katz (1989) examined family, parental, and child-peer interactions along with several physio-logical indices of emotion processes (e.g., stress and emotion regulation) in families with varying levels of marital distress.…”
Section: Other Emotion Regulation Processes: Psychopathological Populmentioning
confidence: 99%
“…The possible roles that emotion understanding and emotion regulation play in the development of psychopathology are suggested by a variety of research findings (e.g., Casey, 1996;Cole, Zahn-Waxler, et al, 1994;Eisenberg, Fabes, Guthrie, et al, 1996;Gottman & Katz, 1989;Hennessy et al, 1994;Seja & Russ, 1999;Southam-Gerow & Kendall, 2000;Zahn-Waxler, Iannotti, et al, 1990). In this final section, we consider how the emotion research we have reviewed impacts clinical research.…”
Section: Synthesis and Future Directionsmentioning
confidence: 99%
“…The dependent variables for verbal responses were ratings on 5-point scales for (a) how angry the arguing adults were perceived to feel, and (b) children's own feelings of anger, sadness, and fear (e.g., Hennessy et al, 1994). Ratings of the selected emotion were entered in analyses (either zero if the emotion was not reported, or the reported intensity of the emotion selected by the child).…”
Section: Data Codingmentioning
confidence: 99%
“…They may misinterpret social interactions as negative and aggressive when, in fact, they are not (Hennessy, Rabideau, & Cicchetti, 1994). At times, they might become dispropor-tionately emotionally upset and distressed when they see others in conflict, and can show exaggerated reactions to these situations.…”
Section: Immediate and Short-term Effects On The Childmentioning
confidence: 99%